Health Sciences Libraries - Bloomfield, Susan; Clark, Deborah; McKelvy, Dina; White, Lucinda (Maine Policy Review, 2013)
Health sciences librarians serve as uniquely trained reference librarians who specialize in the research and dissemination of medical and health information and are an important link to quality health information for patients and consumers. The authors describe how the landscape of health sciences librarianship is constantly changing as new technology emerges, along with librarians' roles within the healthcare system.